Trial Vending Machine Providing Medicine to the Elderly Case Study of Bhakti Luhur Nursing Home - Aga Septi Maulana; Jamaaluddin Jamaaluddin; Syamsudduha Syahrorini (Information Technology and Science (ITScience), 2023)
Vending machine is a machine made to provide various needs of the community. This tool is intended to reduce physical contact in the Covid-19 era and provide Indonesian people experience shopping in the modern era. In this study, a vending machine was made to provide medicines in nursing homes to make it easier for nurses in nursing homes to prepare for the needs of medicines for the elderly who have comorbid diseases such as heart, diabetes, hypertension and shorten time and physical contact in the Covid-19 era. In this research using the ESP8266 microcontroller as a microcontroller and Telegram's IoT (Internet Of Things) for media data base notifications when drugs have been taken. RFID (Radio Frequency Identification) as a card-shaped data identification tool for each elderly person has been programmed according to the diseases suffered by seniors. For the drug dispensing drive system, it uses a servo motor. For information on whether the drugs issued are appropriate, an LCD (Liquid Crystal Display) is added as a display on the vending machine. In this study, the best results were found where all drug inputs issued were in accordance with disease data that had been adjusted to the disease prescription on the RFID tag card.